Hepatitis C in pregnancy: an observational study highlighting its association with maternal parameters - ., Bushra; Ghori, Ambreen; Ahmed, Azra; Dalwani, Najma; Shah, Mushtaque Ali; Ariff, Madiha (International Journal of Research in Medical Sciences, 2019)
Background: Pregnancy is a very crucial time in a woman’s life. In this period of time, not only multiple physiological alterations effect the usual health status but also makes women more vulnerable to contract infection and face negative sequalae. Hepatitis C, a blood borne viral infection serve the similar fate when encountered by pregnant ladies. This study is based on exploring the prevalence of the Hepatitis C virus seropositivity among pregnant population. Moreover, we also evaluated the major risk factors leading to the infection in these mothers. Besides this, infected mothers were studied for their pregnancy outcomes. Methods: In this study 114 pregnant females were observed for this cross-sectional study. It was conducted in Gynecology Unit- 1, Liaquat University Hospital Hyderabad, for the period of January 2017 to July 2017. Chi square test was applied for statistical analysis on SPSS version 16. The criteria for enrollment in the study was set to be a pregnant lady belonging to age group 20-35 years; having singleton pregnancy; was a booked case at the hospital with compliant to antenatal follow ups; admitted to the labor room for delivery. All the non-pregnant ladies, whom had co morbid conditions such as hypertension or diabetes or had infected with hepatitis B or D were excluded from the study. Furthermore, pregnant ladies with multiple gestion or those who were either diagnosed of hepatitis C prior to conceive or had a previous history of hepatitis C were also excluded. Results: Present study revealed that out of 114, 10(8.8%) pregnant ladies were found seropositive for Hepatitis C virus. Prior history for transfusion of blood was the Foremost risk factor discovered, with 60.5% women reported this. History of surgery was the 2nd commonest factor and 43.9% had this in their medical records. On the other hand, only 8.8% women gave the history for previous evacuation. While observing pregnancy outcomes, we found 48.2% neonates had low birth weight, 41.2% were born preterm and 21.1% had low APGAR score. Conclusions: In a nutshell hepatitis c is prevalent in the pregnant population of this region and showing its effects in the form of compromised pregnancies. History of blood transfusion and previous surgery were found to be chief risk factors in the study.